2022
DOI: 10.3389/fnut.2022.874714
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Integrated Maternal Nutrition Intervention Package on Birth Weight in Rwanda

Abstract: Inadequate maternal nutrition before and during pregnancy is a principal risk factor for poor fetal development, resulting in low birth weight (LBW) and subsequently, poor child growth. Most studies focus on the impact of nutritional interventions after birth while only a few interventions consider integrated nutrition service packages. Therefore, there is limited evidence on whether integrated maternal nutrition interventions have a positive effect on birthweight. Thus, a post-program quasi-experimental study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…This implies that nutrition integration had a potential benefit of on the foetal and infant growth and development. Our findings concur with; Veeena et al [34] M Barker et al [8], Von Salmuth et al [10], Olutayo et al [11], Micheal Habtu etal [35] on the effectiveness of a holistic approach to improving the nutritional status of children.…”
Section: Discussionsupporting
confidence: 92%
“…This implies that nutrition integration had a potential benefit of on the foetal and infant growth and development. Our findings concur with; Veeena et al [34] M Barker et al [8], Von Salmuth et al [10], Olutayo et al [11], Micheal Habtu etal [35] on the effectiveness of a holistic approach to improving the nutritional status of children.…”
Section: Discussionsupporting
confidence: 92%
“…All these improved knowledge and skills; in addition, a changed positive mindset regarding nutrition and women empowerment could have affected on the perceived improved nutritional status by addressing both immediate and underlying causes of malnutrition as highly expressed by many of the key informants and FGDs participants in the study. This is supported by quasi-experimental studies conducted by the same authors, which found that the Gikuriro intervention was associated with a significant reduction of low birth weight and maternal undernutrition [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 77%
“…Recent quantitative studies have been performed to evaluate the effect of the Gikuriro program on maternal nutritional status and birth weight. Both postprogram quasi-experiments revealed that the intervention led to significant reduction of low birth weight and maternal undernutrition [ 12 , 13 ]. The main success factor having been attributed to the integration of nutrition-specific and nutrition-sensitive intervention package.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that maternal nutrition during pregnancy has a pivotal role in the regulation of placental-fetal development, that suboptimal maternal nutrition yields LBW [ 46 48 ] and nutritional interventions during pregnancy have been shown to positively affect LBW [ 49 , 50 ]. Thus, the strong association between maternal underweight and LBW that we observed could serve as evidence to support such interventions particularly for WLHIV and primigravidae women.…”
Section: Discussionmentioning
confidence: 99%